Islamizing Smartphones as a Way to Prevent Moral Decline in Early Childhood in the Modern Era - Novriti Ramadora (Academic Solution Publisher, 2024)
This study examines the Islamization of smartphones as an effort to prevent moral decline in early childhood in the modern era. The rapid development of digital technology has made smartphones an inseparable part of everyday life, including in the environment of young children. Although smartphones offer educational and communicative benefits, their uncontrolled use may negatively affect children’s moral development through exposure to inappropriate content, reduced social interaction, and dependency on digital entertainment. This research employed a qualitative library research design by analyzing books, journal articles, regulations, and other relevant scholarly sources related to early childhood, moral education, Islamic values, and smartphone use. The data were collected through documentation techniques and analyzed descriptively and thematically. The findings indicate that the Islamization of smartphones can be carried out by integrating Islamic values into digital use, strengthening parental supervision, selecting age-appropriate religious and educational content, and fostering collaboration between family and educational institutions. The study concludes that smartphone Islamization can serve as a preventive strategy to support moral formation in early childhood, provided that it is implemented consistently, critically, and contextually in accordance with Islamic educational principles.